The Effect of Personal Attitude and Subjective Norm on Entrepreneurial Interest of Biology Education Students - Muliadi, Agus; Mirawati, Baiq (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
Entrepreneurship learning in university becomes a bridge to build students' knowledge, interests, and skills in the entrepreneurial field. As it is to produce graduates who are creative, innovative, productive, reliable, quality, independent, having self-controlled, and competitive. This current research aimed to find out (1) the students' attitudes, subjective norms, and entrepreneurial interests; (2) the influence of subjective norms and attitudes on students’ entrepreneurial interests. It was an ex post facto research with associative descriptive approach. It was conducted in the even semester of 2020 with 56 samples of students of the Biology Education, FSTT Mandalika University of Education who were selcted using purposive sampling technique. The instrument administered was a closed questionnaire about attitudes, subjective norms, and entrepreneurial interests with a Likert scale and  it had been validated by experts. The datawere analyzed using descriptive and inferential statistics with multiple linear regression tests. The results showed that the students’ entrepreneurial attitude had a mean of 3.13 in good category, the subjective norm was 3.13 in good category, and the entrepreneurial interest was 3.08 in good category. Next, the results of multiple linear regression namely (1) the F-test value fell in 16.036 and the significance value of 0.000 was greater than the alpha value of 0.05 (> 0.05). It meant that there was an influence of attitude and subjective norms simultaneously towards students’ entrepreneurial interest; (2) the t-test showed that the significance value of attitude (X1) was 0.033 and the subjective norm (X2) was 0.030 which meant greater than the alpha value 0.05 (> 0.05). It meant that there was a partial influence of attitude and subjective norms on students’ entrepreneurial interest; and (3) the coefficient of determination test showed the value of R Square was 0.377 or 37.7%. It meant that the attitude and subjective norms affected the entrepreneur's interest and the rest of the percentage was affected by other variables or factors.